Factors Predicting Quality of Work Life Perceived by Registered Nurses during the Coronavirus Pandemic 2019 in Srinagarin Hospital, Khon Kaen Province, Thailand - Panphet, Nittaya; Jumpamool, Apinya (Srinagarind Medical Journal, 2022)
Background and objectives: The COVID-19 pandemic have affected the quality of work life perceived by Registered Nurses (RNs). The objectives of this research were to study: (1) the quality of work life perceived by RNs. (2) the compliance with COVID-19 prevention measures. and (3) the predictive ability of personal factors, the compliance with COVID-19 prevention measures, nurse staffing, on quality of work life perceived by RNs. Methods: This study was a predictive correlation study. The samples were RNs of Srinakarin Hospital, 213 people were selected by simple random sampling. Data were collected from April-June, 2022.The questionnaire consists of 1) the practice of preventive measures against COVID-19 and 2) quality of work life perceived by RNs. The questionnaires were CVI yielded .94, 0.90 respectively. Reliability testings were done and reported as α- coefficient of .89 and .96. Using an online method via scanning QR code. Obtained data were analyzed by using descriptive statistics and multiple regression analysis. Results: The quality of work life perceived by RNs were at a high level mean 4.04 ± 0.89. Overall, the compliance with COVID-19 prevention measures was at a high level mean 4.63 ± 0.65. Using regression analysis, personal factors (work experience, average number of work shifts) and the compliance with COVID-19 prevention measures together predicted 21.50% of the variance in quality of working life in positive direction. Conclusion: Working experience, the compliance with COVID-19 prevention measures and appropriate number of work shifts could promote RNs’ quality of working life.